Pengembangan Sistem Informasi Akuntansi Terintegrasi di Perusahaan yang Sedang Bertumbuh (Studi Kasus pada PT Molay Satrya Indonesia) - Haviz Taufik (LPPM Universitas Adiwangsa Jambi, 2022)
The objective of this study is to obtain evidence regarding description of the accounting information system and problems faced by PT Molay Satrya Indonesia, to analyze steps required for the development of accounting information system that is integrated in the PT Molay Satrya Indonesia based on Systems Development Life Cycle (SDLC), and challenges that may be encountered in the development of integrated accounting information system based on the Systems Development Life Cycle (SDLC) method. The development method used in this research was Systems Development Life Cycle (SDLC). The study has been done in two stages which were analysis and conceptual design. This research was used qualitative case study method with data collection. The data analysis used in this study field study, which were included interviewing, observation, and documentation which has been analyzed using data reduction techniques, data presentation, and conclusion. Based on the results of data analysis, information systems owned by PT Molay Satrya Indonesia had not fully integrated between divisions. The next steps required in the development of an integrated accounting system at PT Molay Satrya Indonesia is to identify and evaluate design alternatives that exist. After deciding alternative designs, PT Molay Satrya Indonesia to decide how to meet the needs of the system. There are three ways to do that is to buy the software, develop their own software, and outsourcing system. Challenges faced in the development of a system that is a challenge to human resources, investment, strategic business, technology infrastructure, and supervision and liability.